1998
DOI: 10.1007/s11626-998-0012-2
|View full text |Cite
|
Sign up to set email alerts
|

Positive regulation of normal and tumoral mammary epithelial cell proliferation by fibroblasts in coculture

Abstract: In the mammary gland, mesenchymal-epithelial interactions are of paramount importance during normal and tumoral developments. We have studied the paracrine growth regulation of a variety of breast epithelial cells in coculture with normal or pathological breast fibroblasts. Two models of coculture were used in which the two cell types were seeded and grown, either together in microchamber slides or separated by a microporous membrane. Under these two conditions, all fibroblasts were shown to stimulate the prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 18 publications
3
16
1
Order By: Relevance
“…7 Multiple studies have demonstrated that CAFs have a stronger growth-promoting effect on normal or cancerous breast epithelial cells than NAFs. [31][32][33][34][35][36] Overall, these previous results support our findings indicating that NAFs inhibit the growth of normal or hyperplastic epithelium, but are, in general, less able to alter the growth of cancer epithelial cells.…”
Section: Discussionsupporting
confidence: 91%
“…7 Multiple studies have demonstrated that CAFs have a stronger growth-promoting effect on normal or cancerous breast epithelial cells than NAFs. [31][32][33][34][35][36] Overall, these previous results support our findings indicating that NAFs inhibit the growth of normal or hyperplastic epithelium, but are, in general, less able to alter the growth of cancer epithelial cells.…”
Section: Discussionsupporting
confidence: 91%
“…One of several possible explanations for this discrepancy between the prior result and the present result is a difference in E:F. Shekhar and colleagues used an E:F of 1:1 rather than the E:F of 2:1 we initially used [22]. The number of fibroblasts has been shown to have an effect on the response of epithelial cells [7,9,14]. We therefore repeated the 3D co-cultures of MCF10A cells using NAF-2 and CAF-1 with increasing numbers of fibroblasts (i.e.…”
Section: Resultsmentioning
confidence: 78%
“…In most in vitro analyses, however, direct and indirect co-culture with CAF increased the growth of MCF-7 breast cancer cells compared with MCF-7 cells alone [7,12,14,38]. Co-culture of NAF with MCF-7 cells caused both growth promotion [7,10,11,13,39,40] and inhibition [8] of MCF-7 cells. In contrast, co-culture of NAF and CAF with the breast cancer cell line MDA-MB-231 had no significant effect on epithelial cell growth [10,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mammographically dense area is composed of both stromal and epithelial tissue. Several studies have shown that the stroma can provide a microenvironment that promotes tumor growth, invasion, and metastasis as a result of the interaction between the stroma and breast cancer (van Roozendaal et aL, 1992;Gache et al, 1998;Noel and Foidart, 1998). Epidemiological surveys have already shown that increased breast density is an independent risk factor for breast cancer Harvey and Bovbjerg, 2004).…”
Section: Introductionmentioning
confidence: 99%